The Effect of Green Accounting on Economic Performance (Case Study of Mining and Chemical Industry Sector Companies) - Pratiwi, Nadia Dwi; Ananta, Mufita Dea; Fina, Fatika Rahma; Pandin, Maria Yovita R. (Sekolah Tinggi Ilmu Ekonomi Port Numbay Jayapura, 2023)
This research is motivated by the advancement of science, especially in the field of technology which is very fast, along with competition in the increasingly tight industrial sector where companies have used sophisticated and modern equipment in carrying out their production activities. Research was conducted to examine the effect of Green Accounting on Economic Performance. The quantitative approach method used uses simple linear regression analysis data processing. Return On Assets (ROA) is used for measurement of research variables. The companies as samples for this study were 7 companies in the mining industry sector and the chemical industry sector listed on the IDX for the 2017-2021 period. The results showed that the Green Accounting variable had no positive effect on Economic Performance, as tested through the T-test.